Raman Spectroscopy and Scanning Electron Microscopy Characterizations of Fission Track Method Datable Zircon Grains - Resende, Rosana Silveira [UNESP]; Tello Saenz, Carlos Alberto [UNESP]; Campos Curvo, Eduardo Augusto; Leopoldo Constantino, Carlos Jose [UNESP]; Aroca, Ricardo F.; Nakasuga, Wagner Massayuki [UNESP] (Soc Applied Spectroscopy, 2014)
Spectroscopic and morphological studies, designed to improve our understanding of the physicochemical phenomena that occur during zircon crystallization, are presented. The zircon fission track method (ZFTM) is used routinely in various laboratories around the world; however, there are some methodological difficulties needing attention. Depending on the surface fission track density observed under an optical microscope, the zircon grain surfaces are classified as homogeneous, heterogeneous, hybrid, or anomalous. In this study, zircon grain surfaces are characterized using complementary techniques such as optical microscopy (OM), micro-Raman spectroscopy, and scanning electron microscopy (SEM), both before and after chemical etching. Our results suggest that anomalous grains have subfamilies and that etching anisotropy related to heterogeneous grains is due to different crystallographic faces within the same polished surface that cannot be observed under an optical microscope. The improved methodology was used to determine the zircon fission track ages of samples collected from the Bauru Group located in the north of Parana Basin, Brazil. A total of 514 zircon grains were analyzed, consisting of 10% homogeneous, about 10% heterogeneous, about 20% hybrid, and 60% anomalous grains. These results show that the age distributions obtained for homogeneous, heterogeneous, and hybrid grains are both statistically and geologically compatible.
Keywords: Zircon; Micro-Raman spectroscopy; Fission track method; Scanning electron microscopy; SEM; Zircon grain surface characterization; Zircon chemical etching